EFEKTIFITAS METODE KOLB’S LEARNING DALAM PEMBELAJARAN MATA KULIAH KEWIRAUSAHAAN DI INTERNATIONAL BUSINESS ADMINISTRATION PROGRAM FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SAM RATULANGI - Gunawan, Emilia Margareth; Mandeij, Dennij; Tangkere, Evacuree Svetlana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
This research will contribute to the development of knowledge and application of theory to lecturers, students, and the university, as well as the community in terms of: The research provides the lecturer's benchmark on how or methods to Raises students ' interest in learning entrepreneurship courses, this research can help students to study entrepreneurship courses are more effective and could lead to students ' interest for entrepreneurial, this research can Provide an applied curriculum standard to the university which is titled on a Competency-based lecture system. The results of two-lane equation models in this study show that overall, variables diverging (X1), assimilating (X2), converging (X3) and accommodating (X4) have a significant influence on the effectiveness of learning from The Applied Entrepreneurship Curriculum (Y), thus influencing the student's desire to start his own businessKeywords: Kolb’s Learning Method, Entrepreneuship